Premature Ejaculation and Endocrine Disorders: A Literature Review - Coskuner, Enis Rauf; Ozkan, Burak (KOREAN SOC SEXUAL MEDICINE \& ANDROLOGY, 2022)
Premature ejaculation (PE) is the most common male sexual dysfunction, with 30\% of men experiencing PE worldwide. According to the generally accepted classification, there are two types of PE: lifetime PE and acquired PE. Various biological and psychological causes are known to be involved in the etiology of PE. However, due to the incomplete definition and etiopathogenesis of PE, there is no effective treatment. Although clinical and animal studies indicate that hormones play a role in controlling the ejaculation process, the precise endocrine mechanisms are unclear. In addition, little is known about the role of endocrine disorders in PE etiology. However, there is evidence that diabetes mellitus (DM), obesity, metabolic syndrome (MetS), thyroid gland disorders, pituitary gland disorders, and vitamin D deficiency affect the prevalence of PE. Moreover, it has been reported that the prevalence of PE decreases with treatment of these endocrine disorders. In this review, the relationship between PE and DM, MetS, obesity, vitamin D deficiency, and thyroid and pituitary gland disorders is summarized.
Keywords: Diabetes mellitus; Hyperthyroidism; Metabolic syndrome; Premature ejaculation; Vitamin D